2008
DOI: 10.1093/eurpub/ckn045
|View full text |Cite
|
Sign up to set email alerts
|

Death within 8 days after discharge to home from the emergency department

Abstract: The mortality rate within 8 days of discharge found in the present study is considerably higher than findings in previous studies. Death shortly after discharge of patients with non-causative diagnosis may indicate a misjudgement of the patients' condition at the time of discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…6 These rates are dramatically lower then rates reported in a study conducted in Iceland (0.2% or 208 in 100,000) most likely due to the difference in the health care system, the patient population, and the reliability of the national registry. 7 Our study found the three most common causes of short-term death in patients discharged from the emergency department to be malignancy (19.6%), coronary heart disease (17.3%), and non-atherosclerotic heart disease (11.3%), which includes peri-, endo-, or myocarditis, cardiomyopathy, dysrythmia, pulmonary heart disease and valve disorder. These findings are similar to national statistics in which the most common cause of death in all individuals is due to diseases of the heart (26%) and malignancy (23%).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…6 These rates are dramatically lower then rates reported in a study conducted in Iceland (0.2% or 208 in 100,000) most likely due to the difference in the health care system, the patient population, and the reliability of the national registry. 7 Our study found the three most common causes of short-term death in patients discharged from the emergency department to be malignancy (19.6%), coronary heart disease (17.3%), and non-atherosclerotic heart disease (11.3%), which includes peri-, endo-, or myocarditis, cardiomyopathy, dysrythmia, pulmonary heart disease and valve disorder. These findings are similar to national statistics in which the most common cause of death in all individuals is due to diseases of the heart (26%) and malignancy (23%).…”
Section: Discussionmentioning
confidence: 62%
“…We chose the 7-day time frame because of its clinical relevance, implications for health policy decisions, and prior use in previous studies. 4-7 Mortality data included the California vital statistics files for in-state deaths and the Social Security Death Index for out-of-state deaths. Occurrence of death was determined within the year of the ED visit regardless of subsequent health plan membership status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inpatient admission did not have to originate from a particular visit such as the ED. A 7‐day time frame was selected based on prior studies of adverse events after ED discharge, local quality improvement efforts that often track 7‐day admissions, and an assumption by the research team that longer time frames were likely to include a larger proportion of events unrelated to the index ED visit. If there were more than one ED visits in the 7 days before an admission, the outcome was attributed to only the most‐recent ED visit.…”
Section: Methodsmentioning
confidence: 99%
“…The follow-up period was divided arbitrarily into 8, 15 and 30 days after discharge from the ED to correspond with data from a previous study 20. The follow-up for deaths was also analysed throughout the whole study period to 31 December 2008.…”
Section: Methodsmentioning
confidence: 99%